Insights into the impact of different phytoremediation strategies on antibiotic resistance genes at the metagenomic level in real scenarios - Wei-Guo Zhang; Sizhou Liang; Yonghui Liao; Guangcan Ran; Shenyang Ji; Yan Gao; Zhongfang Lei (Ecotoxicology and Environmental Safety)
Engineered phytoremediation strategies provide cost effective options for eliminating antibiotics and antibiotic resistance genes (ARGs) from wastewater. However, there is a knowledge gap in understanding the impact of these phytoremediation strategies on the on the diversity and composition of ARGs as well as the key driving biotic and biological factors of ARGs at the metagenomic level in real scenarios. Through metagenomic sequencing, this study demonstrates that phytoremediation with Iris pseudacorus L., Myriophyllum verticillatum L., Eichhornia crassipes (Mart.) Solms and Oenanthe javanica (Bl. DC) significantly alters the pattern of antibiotic resistome. This study is the first to reveal, at the omics level, that phytoremediation enhances the diversity of ARGs (3.2 %∼11.6 % improvement), despite reducing their absolute abundances. Furthermore, this study highlights that plant varieties have a significant impact on the performance of phytoremediation in mitigating ARGs. The non-dominant bacterial taxa, specifically Verrucomicrobia, Planctomycetes, and Actinobacteria, play a crucial role in shaping the pattern of the antibiotic resistome during the wastewater treatment. The changes in the total organic carbon, total nitrogen and antibiotics robustly influence the environmental behaviors of antibiotic resistome and microbiome. In summary, this study gives insight into the impact of different phytoremediation strategies on mitigating ARGs at the omics level in real scenarios.